Evolution of the internal structure and physical properties of Tongxin sandstone under high temperature - Guanghui Jiang; Jintao Wang; Jinhao Wen; Jinhao Wen; Xingzong Liu; Bangyong Yu; Bangyong Yu; Yihan Wang (Frontiers in Earth Science)
The stability of the surrounding rock under high temperature is pivotal to the efficient and safe production of high-temperature fluidized mining engineering. To investigate the stability of rocks under high temperature, this paper takes the roof sandstone of Tongxin coal mine, examining changes in its physical parameters such as mass, dimensions, wave velocity, porosity, and permeability after treatment at various temperatures (20–700°C). The results showed that parameters like mass and wave velocity decreased with increasing temperature, while dimensions, porosity, fracture density, and permeability increased. The patterns of change in these physical properties with temperature exhibit a high degree of consistency. Additionally, composition analysis and thermal analysis were conducted to understand the physical and chemical changes occurred in sandstone. Scanning electron microscopy was used to observe microstructural changes in the sandstone. After analysis, the evolution of the internal structure of Tongxin sandstone with heat treatment is categorized into three stages. (1) stable change Stage (20–450°C, 650–700°C): Dominated by dehydration and thermal stress, where pore and fracture structures develop slowly; (2) rapid change stage (450–550°C, 600–650°C): Dominated by the kaolinite dehydroxylation, leading to increased porosity but decreased average pore size; (3) intense change stage (550–600°C): Dominated by the quartz phase transitions, where the thermal stress generated by quartz phase transitions causes dramatic alterations in the internal structure of the sandstone. Furthermore, a correlation model between wave velocity and permeability of sandstone at high temperatures was established based on the interrelationship of these physical properties, providing a new method for real-time monitoring of permeability under high-temperature conditions.